Management of primary psychocutaneous disorders: the role of inflammation in skin-psyche interactions - Astrid, Caroline; Amanda Dharmaningputri, Ni Gusti Ayu; Putri, Muthia Kamal; Rumaisyah, Anna; Pamela, Ruri D. (Dermatology Review/Przegląd Dermatologiczny, 2024)
Psychological factors play an important role in aggravating skin diseases, which could lead to increasing the severity of skin diseases, such as psoriasis, atopic dermatitis, acne vulgaris, seborrheic dermatitis, and lichen simplex chronicus. The interaction between psychological stress and skin disease severity is intertwined with dysregulation of production of proinflammatory cytokines, hormones, and neurotransmitters, which may cause exacerbation of skin diseases. This article aims to thoroughly review the management of skin diseases caused by or closely related to psychological stress from the inflammation pathway point of view, such as psoriasis, atopic dermatitis, acne vulgaris, seborrheic dermatitis, and lichen simplex chronicus. Stress can affect skin through three ways, i.e. as a causal factor for the origin of the diseases, as a trigger of the severity of skin diseases, and as a trigger for the early onset of skin diseases. Psychological stress influences the hypothalamic–pituitary–adrenocortical (HPA) axis hormones by inducing the release of stress mediators, such as neuropeptides and proinflammatory cytokines. It also affects the immune response which might contribute to the worsening of skin diseases. Therefore, psychological stress of the patients needs to be evaluated both before and after the dermatological treatment.